Determinants of the quality of life in Egyptian patients with cerebrovascular stroke by using the stroke specific QoL questionnaire - Arjuman Mohamed Aziz; Alice Edwar Rizian; Fayza Mohamed Tawfik; Jaidaa Farouk Mekky (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2023)
Abstract Background Stroke is a neurological disorder resulting from a sudden decline in blood flow to a localized area of the brain. It is the second most common cause of death and the third most common cause of disability worldwide. Quality of life (QOL) is increasingly being used as an outcome measure designed to evaluate the quality of care for patients with stroke. Objective The study aims to assess the quality of life of cerebrovascular stroke patients in Alexandria, Egypt. Methods A descriptive crossover study was held on 80 adult cerebrovascular stroke patients admitted to the stroke unit at (Elhadra) University Hospital, Neuropsychiatry Department, and the outpatient clinics at the Main University Hospital. Result The main result of study revealed that there was a highly significant relation between socio-demographic characteristics and the patient’s quality of life (QOL), especially age, employment status, and the monthly income, the overall QOL (P < 0.05). Recommendation The study recommended that design health education program to raise stroke patient QOL, design program to improve care giver attitude toward stroke patient, collaborative efforts among the governmental agencies to improve the educational level of the citizens, further studies to examine QOL on larger group of patients to generalize the results.